2022
DOI: 10.24018/ejmed.2022.4.3.1313
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for the Practice of Self-Care Measures Applicable to Mitigate COVID-19 Pandemic

Abstract: Objective: To identify relevant factors influencing the practice of self-care measures for prevention of the ongoing COVID-19 preventions based on prior evidence-based experiences. Method: We conducted a literature review of empirical studies conducted between the years 2000 and 2020 focusing on self-care measures in a pandemic situation. Result: Of the 250 studies identified, 19 studies met inclusion criteria. Sixty-three percent of the eligible studies reported handwashing, 21% reported social distancing, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Adherence to the advice of public health organizations is the result of people's awareness of the danger of the situation, trust in the recommendations of government organizations, and empathy that organizations should attend. 37 The consequences of politicization have affected health and hygiene behavior such as wearing a mask during the Corona pandemic. 38 Living and working in a wide-open space and the need to use masks in closed and crowded spaces were other reasons for not wearing a mask.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to the advice of public health organizations is the result of people's awareness of the danger of the situation, trust in the recommendations of government organizations, and empathy that organizations should attend. 37 The consequences of politicization have affected health and hygiene behavior such as wearing a mask during the Corona pandemic. 38 Living and working in a wide-open space and the need to use masks in closed and crowded spaces were other reasons for not wearing a mask.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic self-medication is prevalent at this time. A recent systematic review reported a global prevalence rate of antibiotics self-medication as 79% [7] and this behaviour is reportedly motivated by the public risk perception [8]. Hence, physicians who should discourage this practice should know about antimicrobial stewardship and mitigate irrational access to antibiotics.…”
Section: Introductionmentioning
confidence: 99%